Upaya Peningkatan Penguasaan Makharijul Huruf melalui Metode Tahsin di Sekolah Vuttisatvitayanuson, Provinsi Krabi, Thailand - Putri, Lusianasta Mandini Hermanto; Muttaqin, Zainal (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
This study aims to explore the impact of the tahsin method in improving the mastery of makharijul huruf (pronunciation of Arabic letters) and Quran reading skills among students at Vuttisatvitayanuson School, Krabi Province, Thailand. The background of this research focuses on the difficulties students face in pronouncing makharijul huruf, which affects the quality of their Quran recitation. The objectives of this study are to identify the students' Quran reading abilities, analyze the implementation of the tahsin method in the learning process, and evaluate its impact on improving the pronunciation of makharijul huruf and the correct application of tajwid rules. This research employs a qualitative approach with a narrative design, where data is collected through interviews and direct observations. Data analysis techniques include data presentation, data reduction, and drawing conclusions. The findings indicate that the implementation of the tahsin method has a positive effect on the pronunciation of makharijul huruf and the correct application of tajwid rules. Furthermore, tahsin learning also plays a role in the development of students' character, such as discipline, responsibility, patience, and attention to detail. Teachers play a key role in providing correct recitation examples and guiding students in improving their reading. The findings suggest that the tahsin method not only enhances the quality of Quran recitation but also contributes positively to the formation of students' moral character, which is highly relevant in the educational context of non-Arab countries like Thailand.